2011
DOI: 10.1021/nn2021875
|View full text |Cite
|
Sign up to set email alerts
|

Nonvolatile Memory Device Using Gold Nanoparticles Covalently Bound to Reduced Graphene Oxide

Abstract: Nonvolatile memory devices using gold nanoparticles (AuNPs) and reduced graphene oxide (rGO) sheets were fabricated in both horizontal and vertical structures. The horizontal memory device, in which a singly and doubly overlayered semiconducting rGO channel was formed by simply using a spin-casting technique to connect two gold electrodes, was designed for understanding the origin of charging effects. AuNPs were chemically bound to the rGO channel through a π-conjugated molecular linker. The π-conjugated bifun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
118
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(119 citation statements)
references
References 40 publications
1
118
0
Order By: Relevance
“…Functionalized graphene and partially reduced graphene oxide (rGO) functionalized on the surface provide possibilities for improving the electrical strength recovery and utilization in devices. Functionalized rGO surface covalently immobilized with metal nanoparticles such as AuNPs and AgNPs, through the organic linkers is a good tool for achieving controllable transport in memory devices [202] and electron transfer in photocatalysis [203]. Click formation of 1,2,3-triazoles on the surface of rGO combined with localized surface plasmon resonance (LSPR) effect of the AuNPs allowed the observation of a fivefold photocurrent enhancement for triazole linkers.…”
Section: Applications Of the Cuaac "Click" Reactionsmentioning
confidence: 99%
“…Functionalized graphene and partially reduced graphene oxide (rGO) functionalized on the surface provide possibilities for improving the electrical strength recovery and utilization in devices. Functionalized rGO surface covalently immobilized with metal nanoparticles such as AuNPs and AgNPs, through the organic linkers is a good tool for achieving controllable transport in memory devices [202] and electron transfer in photocatalysis [203]. Click formation of 1,2,3-triazoles on the surface of rGO combined with localized surface plasmon resonance (LSPR) effect of the AuNPs allowed the observation of a fivefold photocurrent enhancement for triazole linkers.…”
Section: Applications Of the Cuaac "Click" Reactionsmentioning
confidence: 99%
“…Graphene oxide thin films based flexible nonvolatile resistive memory has also been explored [5]. Graphene and graphene oxide have been investigated as FET channel, charge trapping layer and electrode in [14]- [19]. Large hysteresis in the gate characteristics of graphene FETs can be utilized for nonvolatile memory application [20].…”
Section: Introductionmentioning
confidence: 99%
“…A number of reports have utilized graphene or graphene oxide in non-volatile memory devices, such as an FET channel, a charge-trapping layer or an electrode [16][17][18][19][20][21][22] . It was shown that the large hysteresis in the gate characterization curves of graphene FETs (GFETs) can be applied for memory device operation 23 .…”
mentioning
confidence: 99%